Strategi Guru IPS dalam Pembelajaran Berbasis Boarding School pada Siswa Kelas VII di MTs Darul Hikmah Tawangsari Tulungagung - Mohammad Taufik Rifai; Jani Jani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Education is a fundamental right that must be fought for by every child in the nation, and throughout its development, it continues to undergo innovations and evaluations toward better quality. One educational model that is growing in Indonesia is the boarding school system, which has its own characteristics, advantages, and challenges. This study aims to describe the social studies (IPS) teachers’ strategies in boarding school–based learning, the implementation of IPS learning within the boarding school environment, and the obstacles faced by IPS teachers at MTs Darul Hikmah. This research employs a qualitative approach with a case study design. The study was conducted at Pondok Modern Darul Hikmah Tulungagung, with seventh-grade students as research subjects. Data collection techniques included observation, interviews, and documentation. The results show several factors that influence the low effectiveness of IPS learning in boarding schools, including the dense institutional activity schedule that reduces students’ learning focus, teachers’ limited mastery of the subject matter and classroom management, and the dual curriculum implemented simultaneously within the institution. Efforts to improve IPS learning effectiveness include enhancing teacher discipline when entering and leaving the classroom, utilizing audio-visual learning media, and connecting learning materials with current issues to make the lessons more relevant and engaging. Furthermore, the study reveals several advantages of boarding school–based education, such as fostering students’ independence, developing social awareness, providing deeper religious instruction, and integrating both general and religious education. Thus, IPS learning in boarding schools has the potential to develop more optimally with the support of appropriate learning strategies and more structured institutional management.